CONTRIBUTION TO THE KNOWLEDGE OF THE GROUND BEETLE FAUNA FROM SERBIA (COLEOPTERA: CARABIDAE) (Acta Entomologica Serbica, 2014)
During a two-year period of research on the ground beetle fauna in agroecosystems in northern Serbia 19,003 carabid specimens were collected. A total of 67 species from 29 genera were identified. Harpalus distinguendus (Duftschmid, 1812), Amara aenea (De Geer, 1774), Poecilus cupreus (Linnaeus, 1758), and Amara similata (Goeze, 1777) were the dominant species in the winter oilseed rape and winter wheat. The ground beetle genera richest in species were Harpalus, Amara, Calathus, Poecilus and Brachinus. Seven species were new for the ground beetle fauna of Serbia: Calathus cinctus Motschulsky, 1850, Laemostenus complanatus (Dejean, 1828), Brachinus nigricornis Gebler, 1829, Cychrus attenuatus (Fabricius, 1792), Patrobus septentrionis Dejean, 1828, Anchomenus cyaneus Dejean, 1828 and Pterostichus leonisi Apfelbeck, 1904. Three species were recorded for the first time for Vojvodina Province in Serbia: Harpalus signaticornis (Duftschmid, 1812), Harpalus taciturnus Dejean, 1829 and Patrobus atrorufus (Ström, 1768). Newly recorded species were collected in epigeic pitfall traps. Six of them were found in oilseed rape while one was found in winter wheat.